Chaos in the Clinic: Characteristics and Consequences of Practices Perceived as Chaotic. Issue 1 (January 2017) - Perez, Hector R.; Beyrouty, Matthew; Bennett, Katelyn; Baier Manwell, Linda; Brown, Roger L.; Linzer, Mark; Schwartz, Mark D.
Abstract : Abstract: The Minimizing Error, Maximizing Outcome (MEMO) study of clinics in New York City, Chicago, and Wisconsin linked primary care work experiences to physician stress. We analyzed MEMO data to determine how chaos in the clinic was associated with work conditions and quality of care measures. Surveys and medical record audits determined practice characteristics and medical errors, respectively. Physicians rated clinic atmosphere on a scale of 1 (calm) to 5 (chaotic). Chaotic clinics were defined as practices rated either 4 or 5 by greater than 50% of clinic physicians. Forty of 112 MEMO clinics (36%) were chaotic. Compared with nonchaotic practices, these clinics served more minority and Medicaid patients and had a greater likelihood of clinic bottlenecks such as phone access (both p < .01). Physicians in chaotic clinics reported lower work control and job satisfaction, less emphasis on teamwork and professionalism, more stress and burnout, and a higher likelihood of leaving the practice within 2 years (all p < .05). Chaotic clinics had higher rates of medical errors and more missed opportunities to provide preventative services (both p < .05). More research should examine the effectiveness of organizational interventions to decrease chaos in the clinic and to mitigate its effects on patient safety.